CUSTOMER SATISFACTION AND TRUST AS MODERATES THE EFFECT OF PRICE AND SERVICE QUALITY ON PURCHASE DECISION SHOPPING IN THE MARKETPLACE - Mohamad Zein Saleh (Sean Institute, 2023)
Purchasing decisions for a product by consumers who shop through marketplaces are believed to increase if sellers can make prices that match the quality of goods and improve the quality of their services so that buyers will feel satisfied with the goods they have purchased. This study aims to examine, analyze, and find the direct effect of Price and Service Quality on Purchasing Decisions and the indirect effect of Price and Service Quality on Purchasing Decisions through Customer Satisfaction and Trust. This quantitative research uses hypothesis testing to test the nature of the relationship and influence between variables. The statistical analysis used was the AMOS Structural Equation Modeling (SEM). Data was collected using a series of survey research instruments at 4 Marketplaces: Tokopedia, Shopee, Lazada and Blibli, with a sample size of 400. The results showed: 1) Price has a positive and significant effect on purchasing decisions; 2) Service Quality has a positive and significant effect on Purchasing Decisions; 3) Price has a positive and significant effect on customer satisfaction; 4) Customer satisfaction has a positive and significant effect on purchasing decisions; 5) Service Quality has a positive and significant effect on Trust; 6) Trust has a positive and significant effect on purchasing decisions; 7) Price has a positive indirect effect on Purchasing Decisions through Customer Satisfaction and 8) Service Quality has a positive indirect effect on Purchase Decisions through Trust